Becoming the beheld: Iran’s media ecology and the question of superficial imitation - Moazami, M (Intellect, 2019)
What exactly is this televisual cultural identity that seems to be emerging among Iran’s more cosmopolitan-minded youth ‐ this culture founded on the emulation of Euro-American pop cultural values, this culture where what is seen on-screen is often taken for face value and translated accordingly into actual lifestyle choices of the viewing audience? In fact, beyond the media from which these performances are imitated, the phenomenon itself is not altogether new. From the late nineteenth century through to the twenty-first century, terms such as gharbzadegi (‘Occidentiotis’ or ‘Weststruckness’) and ‘cultural schizophrenia’ have encompassed the civilizational discourse with respect to Iran and its purported superficial imitation of the western world. This article wishes to expand on these inquiries by applying to them a distinctly media ecological lens. Borrowing from the theories of Marshall McLuhan and Walter Ong, this work summarily investigates the effects that media, including print, photography and radio have had on the Iranian milieu. This study hopes to introduce a new lens with which to study Iran’s media environment.